KETIMPANGAN KONTRA KARYA PT FREEPORT INDONESIA - Rumadan, Salmawati _; ., Rumainur (TAHKIM, 2022)
The purpose of this study is to find out from the contract of work of PT Freeport Indonesia, the general description of PT Freeport Indonesia, , the problem of the PT. Freeport Indonesia , Freeport Indonesia's Hunting Wages Inequality and the Impact of Mining on the Environment. The approach method used in this research is normative, with research specifications namely normative juridical, which is a study that reviews positive legal provisions, legal principles, and legal doctrines in order to answer the legal problems faced. The primary data used are legal materials that bind directly, legal materials in the form of laws and regulations. Secondary data (library research) secondary data from legal materials that provide instructions and explanations for primary and secondary legal materials. The result of this research is how the form of PT Freeport Indonesia's contract of work, the problem of the PT. Freeport Indonesia, Freeport Indonesia's Hunting Wages Inequality and the Impact of Mining on the Environment